Gender Differences in Cardiovascular Risk and Psychological Stress among Adults in Pakistan - Huma Naeem Tareen, Muhammad Abbas, Maria Shahzad, Farrukh Iqbal, Asad Ullah, Ashfaq Hussain (Pakistan Journal of Medical & Health Sciences, 2024)
Purpose: This paper set out to evaluate gender differences in cardiovascular risk factors and psychological stress in adults in Quetta, Pakistan, and to determine the relationship between perceived stress and cardiovascular risk in both male and female participants. Procedure: A cross-sectional analytical study was developed among adult participants aged between 30 years and above in Quetta in Baluchistan during the period from February 2023 to August 2023. A structured questionnaire was used to collect data on socio-demographic factors, lifestyle, medical history, smoking status, physical activity, family history of cardiovascular disease and psychological stress. Perceived stress was measured using the Perceived Stress Scale and cardiovascular risk was measured using clinical and behavioural risk indicators such as blood pressure, body mass index, diabetes status, history of hypertension and lipid-related risk information where available. Descriptive statistics, chi-square test, independent sample t-test, and logistic regression were used to compare male and female participants and identify factors that were associated with an increased cardiovascular risk. Findings: The analysis exhibited significant gender disparities in cardiovascular risk and psychological patterns of stress among the adults in Quetta. The female participants were more exposed to the psychological stress than their male counterparts, and the males were also more exposed to the behavioural risk factors such as smoking and sedentary lifestyle. Risk factors in both genders that were mostly observed included hypertension, increased body mass index, diabetes, and family history of cardiovascular disease. Participants that had greater perceived stress scores had an increased likelihood of having greater cardiovascular risk indicators. The correlation between psychological stress and cardiovascular risk seemed to be stronger in females, indicating that stress may have a different effect on cardiovascular vulnerability between the genders. Conclusion: Gender variations are significant in the distribution of cardiovascular risk and psychological stress in adult people in Quetta. It was observed that psychological stress was a significant factor that was linked to cardiovascular risk especially in women. These results indicate that gender sensitive cardiovascular prevention programs, routine stress screening, lifestyle change and early screening program are required in Quetta and other cities in Pakistan of similar size. Keywords: Gender differences, cardiovascular risk, psychological stress, hypertension, perceived stress, Quetta, Pakistan, adults.